Evolution and drivers of secondary suspended rivers in typical wandering sections of the lower Yellow River from 1960–2021 - Xu, Linjuan; Li, Junhua; Xu, Haifan; Zhang, Xiangping; Lai, Ruixun; Zhang, Xiang; Gao, Xiangyu (Frontiers in Ecology and Evolution, 2023)
The secondary suspended river increases the probability of the occurrence of "Heng river" "Xie river" and "Gun river" in the lower Yellow River, and is the main factor threatening the safety of human life and property in the Yellow River levee and beach area. Here, the Dongbatou-Gaocun section of the severe secondary suspended river in the lower Yellow River was taken as the research object. The trend and periodicity of the evolution characteristics of the secondary suspended river in the study area from 1960-2021 were systematically analyzed using the Theil-Sen estimator and wavelet analysis, and the factors influencing its development were quantitatively explored. Over the past 62 years, development of secondary suspended rivers can be divided into four stages: initial formation (1960-1973), slow development (1974-1986), rapid development (1987-1999) and stable periods. The evolution period of the beach transverse gradient differed significantly before and after operation of Xiaolangdi Reservoir commenced, prior to which there was a first main period of 31 years followed by a second main period of 21 years. Development of secondary suspended rivers was primarily related to floodplain flooding and human activity. When the inflow sediment coefficient of a floodplain flood (ζ) was < 0.04 and the floodplain coefficient was < 1.29, the secondary suspended river was relieved; when ζ > 0.04 or ζ < 0.04 and the floodplain coefficient was > 1.29, the secondary suspended river was intensified. The production levees have exacerbated development of secondary suspended rivers to some extent.